2022
DOI: 10.1155/2022/5275449
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Sustainable Agriculture by Arbuscular Mycorrhiza under Stress Condition: Mechanism and Future Prospective

Abstract: Global agriculture is frequently subjected to stresses from increased salt content, drought, heavy metals, and other factors, which limit plant growth and production, deteriorate soil health, and constitute a severe danger to global food security. Development of environmentally acceptable mitigation techniques against stresses and restrictions on the use of chemical fertilizers in agricultural fields is essential. Therefore, eco-friendly practises must be kept to prevent the detrimental impacts of stress on ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 313 publications
0
4
0
Order By: Relevance
“…Strigolactones are a class of plant hormone that participate in the detection of fungal structures and establishment of AM symbiosis in the host plants (Chauhan et al 2022). They are also involved in regulatory roles against abiotic stress.…”
Section: Modulation Of Phytohormonesmentioning
confidence: 99%
“…Strigolactones are a class of plant hormone that participate in the detection of fungal structures and establishment of AM symbiosis in the host plants (Chauhan et al 2022). They are also involved in regulatory roles against abiotic stress.…”
Section: Modulation Of Phytohormonesmentioning
confidence: 99%
“…Especially microbial fertilizer, which is considered to be one of the most promising means to improve the productivity of the crop in an environment-friendly manner. Microbes present in microbial fertilizers play a pivotal role in optimizing various activities like organic matter decomposition, plant nutrient absorption such as that of potassium, nitrogen, phosphorous in plants ( Milton et al, 2020 ; Chauhan S. et al, 2022 ; Rani et al, 2022 ; Upadhyay et al, 2022b ). Several studies have shown that the co-application of biochar and other fertilizers is better than the application of biochar or fertilizer alone ( Naeem et al, 2017 ; Li et al, 2018 ; Cui et al, 2020 ; Bai et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AMF secrete enzymes that degrade organic phosphorus compounds into forms that plants can easily absorb [16,17]. This heightened phosphorus acquisition enables plants to get through constraints in nutrient availability and bolster their growth and development [18]. Additionally, AMF have been discovered to have an effect on nitrogen uptake and assimilation in plants.…”
Section: The Influence Of Amf On Plant Nutrient Distributionmentioning
confidence: 99%